Relationship with Programmed Cell Death Ligand 1 (PD-L1) and DTI Features in Brain Metastases of Non-small Cell Lung Cancer: A Preliminary Study - Yilmaz, Temel F.; Yurtsever, Ismail; Turk, Hacı Mehmet; Gultekin, Mehmet Ali; Besiroglu, Mehmet; Cesme, Dilek Hacer; Shbair, Abdallah T M; Alkan, Alpay (Current Medical Imaging, 2021)
Objective: The purpose of the study was to determine DTI properties of brain metastases in subjects with Non-Small Cell Lung Carcinoma (NSCLC) to evaluate whether there was a correlation between DTI findings and Programmed Cell Death Ligand-1 (PD-L1). Methods: The study population (n:22) was assigned to PD-L1 negative (Group 1: PD-L1 expression<% 50) (n=11) or positive (Group 2: PD-L1 expression ≥%50) (n=11). We compared ADC and FA values measured from the enhanced solid metastases and peritumoral edema area with PD-L1 protein status. Results: The mean ADC values were lower in group 2 compared to group 1. The peritumoral ADC values were higher in group 2 compared to group 1. Mean peritumoral edema FA values were lower in group 2 compared to group 1. The peritumoral edema nADC values were higher in group 2 compared to group 1. As PD-L1 expression frequency increased, ADC values in the peritumoral edema area increased and FA values decreased. Conclusion: We thought that the existence of PD-L1 protein does not affect ADC and FA values of brain metastasis (BM) originating from NSCLC. DTI characteristics of the peritumoral edema area could be a guide in determining the PD-L1 protein status of brain metastases of NSCLC. The relationship between PD-L1 expression status and DTI features in BM from NSCLC could help us to have an idea regarding the response to immunotherapy.
Keywords: Programmed cell death ligand 1